Response of Iron and Cadmium on Yield and Yield Components of Rice and Translocation in Grain: Health Risk Estimation - Siddique, Abu Bakkar; Rahman, Mohammad Mahmudur; Islam, Md. Rafiqul; Mondal, Debapriya; Naidu, Ravi (Frontiers in Environmental Science, 2021)
Rice consumption is a major dietary source of Cd and poses a potential threat to human health. The aims of this study were to examine the influence of Fe and Cd application on yield and yield components, dynamics of Cd in pore water, translocation factors, daily dietary intake, and estimation of human health risks. A pot experiment was performed under glasshouse conditions where rice cultivars (Langi and Quest) were cultivated in two dissimilar soils under different levels of Cd (0, 1.0, and 3.0 mg kg−1) and Fe (0, 1.0, and 2.0 g kg−1). The results showed that variation in two rice cultivars in terms of yield and yield-related components was dose dependent. Cadmium concentration in soil pore water was decreased over time and increased with increasing Cd levels but decreased with Fe application. Translocation factors (TFs) from root to straw (TFroot-straw) or straw to husk (TFstraw-husk) were higher than root to grain (TFroot-grain) or straw to grain (TFstraw-grain). The Quest cultivar had 20% lower Cd than the Langi cultivar. Application of Fe at the rate of 1 and 2 g kg−1 soil reduced Cd by 23 and 46%, respectively. Average daily intake (ADI) of Cd exceeded the permissible limit (5.8 × 10−3 mg −1 kg−1 bw per week) when rice plant subjected 1 and 3 mg kg−1 Cd stress with or without Fe application. Results also indicated that ADI value was lower in the Quest cultivar as compared to the Langi cultivar. Estimation of human health risk revealed that the non-carcinogenic risks (HQ > 1) and carcinogenic risks (CR > 1.0 × 10−4) increased with increasing Cd levels in the soil. The application of Fe decreased the human health risks from rice consumption which is more pronounced in Fe 2.0 than in Fe1.0 treatments. The rice cultivar grown in soil-1 (pH 4.6) showed the highest health risks as compared to soil-2 (pH 6.6) and the Quest cultivar had lower health risks than the Langi cultivar.